Production of Fuel Bioadditive "Triacetin" Using a Phosphomolybdic-Acid-Loaded PVA Membrane in a Pervaporation Catalytic Membrane Reactor - Ünlü, Derya; Hilmioglu, Nilufer Durmaz (Amer Chemical Soc, 2019)
The objective of this article is to synthesize fuel bioadditive triacetin by the innovative membrane process with high yield under mild operating conditions. A phosphomolybdic-acid-loaded poly(vinyl alcohol) (PVA) membrane was prepared as a composite catalytic membrane. The composite catalytic membrane was placed in a membrane reactor cell. Water was separated continuously from the reaction medium using a pervaporation process for the improvement of glycerol conversion and triacetin selectivity. The effects of the operation conditions on glycerol conversion, triacetin selectivity, and separation performance were examined in detail. Although the glycerol conversion was 53% for 7 h using the phosphomolybdicacid-loaded PVA membrane pieces in the batch reactor, this value was 100% in 7 h using a phosphomolybdic-acid-loaded PVA membrane under the same operating conditions (reaction temperature 75 degrees C, catalyst concentration 5 wt %, and molar feed ratio 6:1) in the esterification coupled with pervaporation system. Furthermore, although triacetin selectivity was 0.6% in a batch reactor, this value was 76% in esterification coupled with a pervaporation process. As a result of the study, the esterification coupled with a pervaporation process was found to be an efficient process for the synthesis of triacetin with high selectivity.
Keywords: [No Keywords]